Sri Lanka : Staff Report for the 2016 Article IV Consultation and Request for a Three-Year Extended Arrangement under the Extended Fund Facility-Press Release; Staff Report; Staff Statement, and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses economic performance, outlook, and risks of Sri Lankan economy. Macroeconomic performance in 2015 reflected a mix between positive underlying growth momentum, the negative impact of unbalanced domestic policies, and an increasingly difficult external environment. The government fiscal deficit expanded to 6.9 percent of GDP in 2015. The overall balance of payments deteriorated significantly in 2015 despite an improvement in the terms of trade. Sri Lanka's short-term outlook is challenging, but medium-term prospects are favorable if current macro-financial imbalances can be addressed. The key risks to the outlook stem from (1) government inaction on key policies and (2) a significant deterioration in the external environment.